PENGARUH KOMUNIKASI, MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN CAHYA PRIVATE MENGEMUDI DENPASAR - Ni Ketut Ari Pramesti; Sapta Rini Widyawati; Putu Ayu Sintya Saraswati (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2023)
Every company will always try to get the best performance from its employees in the hope that the company's goals will be achieved. The success of a company is strongly influenced by the performance of its employees. This study aims to determine the effect of communication, work motivation and work environment on employee performance. This research was conducted at Cahya Private Driving Denpasar. The sample in this study were 58 employees at Cahya Private Driving Denpasar. The method of determining the sample in this study is the saturated sampling method. Data was collected through observation, questionnaires and documentation. The data analysis technique used in this study is linear regression analysis through the SPSS version 25 program. Based on the results of the analysis, this study shows that communication has a positive and significant effect on employee performance at Cahya Private Driving. The more communication that exists at Cahya Private Driving, the employee's performance will increase. Work motivation has a positive and significant effect on employee performance at Cahya Private Driving. The more work motivation in Cahya Private Driving increases, the employee's performance will increase. The work environment has a positive and significant effect on employee performance at Cahya Private Driving. The more the work environment in Cahya Private Driving increases, the employee's performance will increase.